Fermented drink elaborated with lactic acid bacteria isolated from chiapaneco traditional pozol - Velázquez-López, Arturo (Universidad Autónoma de Tamaulipas, 2018)
One of the main residues in Chiapas comes from the cheese industry, whey, which contains high quality nutrients (lactose 4.5 %, soluble proteins 0.7 % and bioactive peptides). By containing optimum amounts of sugars, it is a good source for fermentation by means of lactic acid bacteria (LAB). In Chiapas, there are typical fermented beverages, one of which is pozol, which contains many beneficial microorganisms. Therefore, the following research was carried out, which consisted of isolating, identifying and evaluating the fermentation capacity of lactic acid bacteria, as well as the probiotic potential, from the fermented chiapaneco pozol, to make a whey-based beverage added with jam of pineapple-coconut flavor. Firstly, BAL were isolated, and identified through basic biochemical tests. Those with the greatest fermentative capacity and probiotic potential were then selected. The level of enjoyment was evaluated by a group of 20 untrained judges (14 and 20 years). The biochemical tests and probiotic potential showed that the fermented pozol contains bacteria beneficial to human consumption: therefore, it was considered probiotic drink. The fermented beverage with the pozol strain showed the highest level of liking (P < 0.05) and 2 x 107 CFU/mL. The results of this study open up the possibility for the use of whey in the preparation of fermented beverages with probiotics and good organoleptic  acceptance.